Mistakes in using Keigo on Japanese Busines Correspondence Subject - Timur Sri Astami (Bina Nusantara University, 2009)
Keigo style is honorific form in Japanese Language in which the language learners get difficulties in learning, especially the third semester of Bina Nusantara students. Keigo style is divided into sonkeigo, kenjougo, and teineigo. Article presented students’ mistakes in using keigo, especially sonkeigo dan kenjougo. It is noted that keigo has a relationship between the speaker (messenger), the receiver (mitra tutur), and the situation that all of them were called taiguu hyougen. The results indicate that the students get accidently exchanged in using sonkeigo and kenjougo, vice versa. If it is applied in question sentences, 60% of the students cannot answer it. Used in presenting condition, 60% of the students cannot answer, while used in presenting requirement, 50% of students cannot answer, and used in presenting permission, 40% of students cannot use this keigo style. It can be concluded that the average of 53% of students are not able to use keigo style.